Admission hyponatraemia as heart failure events predictor in patients with acute heart failure - Yuke Sarastri; Juang Idaman Zebua; Puja Nastia Lubis; Fathi Zahra; Anggia Chairuddin Lubis (ESC Heart Failure, 2023)
Abstract Aims Heart failure remained consistent as one of the biggest cardiovascular problems in Indonesia. Hyponatraemia is a common electrolyte disorder among patients presented with heart failure; however, the prognostic value for worsening heart failure has not been well defined. Methods and results We studied 134 patients admitted with acute heart failure and investigated the relationship between admission serum sodium and the composite clinical outcomes of all‐cause mortality and hospitalization ambispectively with a follow‐up duration of 6 months. We also try to look for low sodium‐level impacts in several conditions. Among 134 patients, 84 patients presented with low sodium during admission, defined as a serum sodium level of <135 mEq/L, and it was associated with higher composite clinical outcome risk [odds ratio (OR), 5.9; 95% confidence interval (CI), 2.8–12.0; P < 0.001]. Moreover, hyponatraemia impacts on composite endpoints were driven by both parameters; it was independently associated with mortality (OR, 3.1; 95% CI, 1.4–6.8; P = 0.003) and rehospitalization (OR, 5.3; 95% CI, 2.4–11.7; P < 0.001). This result remained consistent in most subgroups. Conclusions On‐admission hyponatraemia is a predictor for 6 month mortality and rehospitalization. Further work is needed to determine if correction of hyponatraemia translates into clinical benefit.